2021
DOI: 10.5194/hess-2021-614
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep Learning Methods for Flood Mapping: A Review of Existing Applications and Future Research Directions

Abstract: Abstract. Deep Learning techniques have been increasingly used in flood risk management to overcome the limitations of accurate, yet slow, numerical models, and to improve the results of traditional methods for flood mapping. In this paper, we review 45 recent publications to outline the state-of-the-art of the field, identify knowledge gaps, and propose future research directions. The review focuses on the type of deep learning models used for various flood mapping applications, the flood types considered, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 88 publications
1
10
1
Order By: Relevance
“…Both U-Net and RF models were skillful in predicting water depth within the training domain (minimum NSE=0.6). Contrary to the hypothesis that deep learning algorithms were superior to shallow machine learning algorithms (Bentivoglio et al, 2022), the results suggested that the RF models outperformed the U-Net models for predictions within the training domain. However, we found that the high performance of RF models was largely owed to overfitting: outside of the training domains, RF models exhibited a substantial performance loss for all considered metrics (NSE, RMSE, and CSI).…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Both U-Net and RF models were skillful in predicting water depth within the training domain (minimum NSE=0.6). Contrary to the hypothesis that deep learning algorithms were superior to shallow machine learning algorithms (Bentivoglio et al, 2022), the results suggested that the RF models outperformed the U-Net models for predictions within the training domain. However, we found that the high performance of RF models was largely owed to overfitting: outside of the training domains, RF models exhibited a substantial performance loss for all considered metrics (NSE, RMSE, and CSI).…”
Section: Discussioncontrasting
confidence: 93%
“…In contrast to U-Net models, TWI was not among the most important predictive features for the RF models. The estimated best predictive features from the U-Net and RF models were not the same but the results agree with the findings in the literature that TWI (Jalayer et al, 2014;Seleem et al, 2021;Bentivoglio et al, 2022),SDepth (Zhang and Pan, 2014;Seleem et al, 2021) and altitude (Zhang and Pan, 2014;Seleem et al, 2021Seleem et al, , 2022 are indicators for urban flood-prone areas.…”
Section: Feature Importancesupporting
confidence: 85%
See 1 more Smart Citation
“…Image segmentation, whereby each pixel is classified into predetermined classes (e.g., 'sand,' 'water,' 'vegetation'; see Figure 3), facilitates spatially explicit mapping of coastal environments. Image segmentation methods have been useful for estimating landcover types (Buscombe and Ritchie, 2018), backshore morphology (Mao et al, 2022), roughness for flood models (Sherwood et al, 2021), mapping flood extents (Erdem et al, 2021, Bentivoglio et al, 2021, flood damage (Adriano et al, 2021), and economic impacts (Donaldson and Storeygard, 2016). Segmentation and classification methods can also be slightly modified into so-called "image regression" methods, which provide continuous estimates of quantities of interest (e.g., wave height - Buscombe et al, 2020) or water depth (Collins et al, 2020).…”
Section: Satellite Image Classification Segmentation and Regressionmentioning
confidence: 99%
“…This success can be largely attributed to the generalizing power of CNNs toward spatiotemporal patterns in the data, specifically including contextual signatures, closely mimics human interpretation given enough training data. CNNs have already been successfully applied to various problems in the earth observation domain, including water and flood mapping using either optical or radar data (e.g., Bentivoglio et al 2021;Wieland and Martinis 2019;Li et al 2019a, b;Bonafilia et al 2020;Nemni et al 2020;Katiyar et al 2021;Bai et al 2021;Helleis et al 2022).…”
Section: Open Rural Areasmentioning
confidence: 99%